Low level of Cyclooxygenase-2 transcript in the spleen of lymphoma rats supplemented with garlic powder - Hamzah, Hazilawati; Ahmad Sayuti, Nurul Syahirah; Mohd Iffendi, Sajjaratul Nurul Nadia Asyura; Ali Salih, Hutheyfa Abd Alhussein; Shaari, Mohd Rosly; Wan Mohd Zain, Wan Somardi; Mohd Esa, Norhaizan; Sithambaram, Shannugavelu; Mohamed Mustapha, Noordin; Sabri, Jasni (Innovare Academic Sciences, 2016)
Cyclooxygenases (COXs) regulate tumor cell proliferation and metastasis in many types of cancers including hematological cancers. Organosulfurs derived from garlic have a potential to inhibit the expression of COX-2 in cancer patients. Objective: In this study, we evaluate the transcription levels of COX-2 in the spleen of lymphoma rats supplemented with garlic powder. Methods: Three groups of rats were equally divided into control (n=3), lymphoma (n=3), and lymphoma supplemented with garlic powder (n=3) groups. Lymphoma was induced via administration of N-methyl-N-nitrosourea (MNU) intraperitoneally 4 times in 2 week periods. Garlic powder mixed with ground commercial rat diet was given daily at 5% of feed intake, starting at day 1 of MNU exposure. All rats were kept for 24 weeks before spleen samples were collected and extracted for total RNA. The transcription levels of COX-2 transcript in the total RNA were determined using quantitative real-time reverse transcriptase polymerase chain reaction assay. The total RNA was converted into cDNA followed by amplification of COX-2 and beta-actin genes. Results: Results of the amplification of COX-2 transcripts were normalized with the housekeeping gene, beta-actin. The relative transcription level of COX-2 transcript in the spleen of lymphoma rats was 1.941±0.131 fold higher (p<0.05) than control rats (1.00±0.001 fold), while the transcription levels in the spleen of lymphoma rats supplemented with garlic was significantly lower (0.423±0.239 SE fold) than the lymphoma rats that received no supplementation of garlic powder. Conclusion: The findings suggest that garlic powder reduces the transcription of COX-2 transcript in the spleen of lymphoma rats.